2020
DOI: 10.1111/ctr.13801
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged extracorporeal preservation and evaluation of human lungs with portable normothermic ex vivo perfusion

Abstract: Many lung donor offers are refused despite increasing demand. Portable normothermic ex vivo lung perfusion (EVLP) could increase donor yield by monitoring and reconditioning extended criteria donor (ECD) lungs. We report its use in human lungs declined for clinical transplantation. Ten sets of such lungs were procured from brain‐dead donors and underwent 24 hours of normothermic EVLP using a perfusate based on donor whole blood. Hemodynamic and ventilatory data and P:F ratios were measured. Advanced donor age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…When analyzing donor lung quality, oxygenation capacity was long seen as the most important parameter for assessing lungs before and during EVLP. There is increasing evidence that overall graft performance during EVLP is more important for evaluation ( 7 , 13 , 15 , 16 ). A study by Yeung et al, in which an acellular perfusate was used, demonstrated that while compliance and airway pressure deteriorated, oxygenation remained stable.…”
Section: Discussionmentioning
confidence: 99%
“…When analyzing donor lung quality, oxygenation capacity was long seen as the most important parameter for assessing lungs before and during EVLP. There is increasing evidence that overall graft performance during EVLP is more important for evaluation ( 7 , 13 , 15 , 16 ). A study by Yeung et al, in which an acellular perfusate was used, demonstrated that while compliance and airway pressure deteriorated, oxygenation remained stable.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma component of ADWB might alleviate IR injury through antifibrinolytic mechanisms during EVLP. 93,94 Inventors later described a technique to collect ADWB during multiorgan procurement surgery. 95 ADWB-based perfusate and plasma exchange have also been shown to provide optimal conditions for ex vivo heart perfusion.…”
Section: Blood (Cellular Versus Acellular Perfusate)mentioning
confidence: 99%
“…At current, experimental, mostly porcine, setups report stable EVLP for up to 72 hours ( 5 , 7 ). Clinical implementation of these prolonged protocols is still lacking.…”
Section: Introductionmentioning
confidence: 99%